Millets as a Pathway to Sustainable Livelihoods in Nepal - Joshi, Hari Prashad; Gyawali, Saroj; Ghimire, Hari Prasad; Patali, Chakra Bahadur (The Journal of Economic Concerns, 2025)
In Nepal, millets which resist climate change have been important for the country’s farming, culture and nutrition for a long time. Using the Sustainable Livelihoods Framework (SLF), this study studies the many ways millet contributes to improving rural livelihoods, demonstrating its support to natural, human, social, physical and financial assets. Farmers grow millets on lands with little water because they use less water than other grain crops like rice. Still, limited yield growth, trouble finding workers and scattered supply networks block their ability to develop economically. The nutritional value of millets helps deal with common deficiencies, since they contain plenty of iron, calcium and fiber to protect against malnutrition and anaemia. Yet, there are still some problems: unpredictable rain, lack of support from policies and limited chances to sell their products stop development. Climate-smart meat and dairy farming, creating snack products and serving customers who seek healthier foods can be strategies moving forward. In Dolakha and Karnali, agricultural cooperatives and initiatives supported by Food and Agriculture Organization (FAO) increased both yields and incomes. The research wishes governments to integrate policies focused on researching new drought-resistant millet breeds, building better millet processing factories and informing people about the benefits of millet. When millet promotion goes alongside Nepal’s Climate-Smart Agriculture and Sustainable Development Goals, stakeholders have a chance to turn this grain into a major part of fair, climate-safe development, protecting food security and jobs among those at risk.